Child and adolescent online risk exposure : an ecological perspective - Wright, Michelle F.; Schiamberg, Lawrence B. (Academic Press, 2021)
Focuses on online risks and outcomes for children and adolescents using an ecological perspective (i.e., the intersection of individuals in relevant contexts) for a better understanding of risks associated with the youth online experience. The book examines the specific consequences of online risks for youth and demonstrates how to develop effective and sensitive interventions and policies. Sections discuss why online risks are important, individual and contextual factors, different types of risk, online risks among special populations, such as LGBT youth, physically or intellectually disabled youth, and ethnic and religious minorities, and intervention efforts. Examines online risks such as problematic internet use, contact risk behaviors, online exploitation, online hate, cyberbullying, and cyberstalking Explores the concept of digital citizenship Includes theoretical considerations and the prevalence of online risks Covers policy and intervention recommendations for reducing online risks.